Parental difficulties during online learning process - Sarair Sarair; Ayuna Netta; Novi Wulan Lestari (ACCENTIA: Journal of English Language and Education, 2022)
This study aimed to investigate the problems that parents faced and how they dealt with them during the online learning process. The study used the qualitative research method. The study enlisted 10 people (parents) as the participants to describe the type of issues that arose during the online learning process. The data were then examined through data reduction, data display, and conclusion drawing. The findings revealed that parents faced a variety of issues that hampered the learning process; the issues were primarily caused by a lack of a good phone, internet data, and poor connection. The study suggests that in order to fix the problems, parents should contact the teachers and seek help from others.